Cradle of Freedom : Alabama and the Movement That Changed America - Gaillard, Frye, 1946- (Book collections on Project MUSE., 2015)
Cradle of Freedom puts a human face on the story of the black American struggle for equality in Alabama during the 1960s. While exceptional leaders such as Martin Luther King Jr., Rosa Parks, Fred Shuttlesworth, Ralph Abernathy, John Lewis, and others rose up from the ranks and carved their places in history, the burden of the movement was not carried by them alone. It was fueled by the commitment and hard work of thousands of everyday people who decided that the time had come to take a stand. Cradle of Freedom is tied to the chronology of pivotal events occurring in Alabama the Montgomery b.